(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article deals with the structural-semantic peculiarities of the typical word-building paradigm of the verbs with the prefixes of dynamic spatial localization in the Ukrainian and Polish languages. The research determines the structure of the common word-building paradigm – substantive-adjective-verbal-adverbial – and reveals the typology of semantic positions of every zone (“an executor of the action”, “a subjectified action”, “a place of the action”, “an object”, “an instrument of the action” – in the substantivized zone; “an attribute of the object”, “an attribute of the subject”, “intended for what the inventive stem points out” – in the adjectival zone; “with the help of the action called by the verb, transfer (transferred) from somewhere else all or lots”, “performing an action to transfer something from the state of the object to the state of the subject” – in the verbal zone; “adverbialization of the action” – in the adverbial zone). The investigated verbs of the Ukrainian language realize all the meanings of the typical word-formative paradigm, in the Polish language has been not discovered derivatives with word-formative meaning “intended for what the forming verb appointed”. Among the deverbals of the two comparative languages the greatest number of nouns has been noted. It is proved that the word-building meaning “a subjectified action” is characterized by the largest depth of the places (ukr. зіскок, зскакування; скид, скидка, скинення, скидання та ін.; pol. osuwanie, osunięcie, osuw, osunienie; spad, spadek, spadanie, spadnienie, spadnięcie). Nouns with this meaning in the Polish language are quantified the Ukrainian deverbals almost in twice. It is stated that some nouns with the meaning “object-related actions” are not even fixed in explanatory dictionaries; the set of word-building meanings which explicate word-building meanings and quantitative admission of the zones and semantic positions is defined. None of the verbs has implemented all the word-formation meanings of a typical word-formative paradigm.